For Better or Worse - Sinenhlanhla Sithulisiwe Chisale (African Journal of Gender and Religion (AJGR))
This article argues that intimate wife abuse and gender-based violence (GBV) is fuelled by premarital counselling. The extent to which Christian and traditional indigenous premarital counselling encourage GBV in marriage contexts by promoting “dangerous masculine and feminine” conceptualisation of marriage, is explored via an autoethnographical methodology and an African feminist critical hermeneutics approach. Findings indicate that the pedagogies of the traditional and Christian premarital counselling are gendered in a way that promotes and justifies intimate wife abuse in marriage contexts complicating women’s struggle with GBV.